ANALISIS PEMBERIAN UJRAH BAGI PEMILIK LAHAN UNTUK KESEJAHTERAAN BURUH HARIAN LEPAS DESA LUBUK TABUN KEC.TANJUNG SAKTI PUMI KAB. LAHAT - Lupita; Isnaini, Desi; Cahyono, Andi; Alimuddin, Agus (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2024)
This research aims to find out how giving Ujrah to land owners improves the welfare of casual daily workers in Lubuk Tabun Village, Tanjung Sakti Pumi District. Lahat. This type of research uses qualitative descriptive research with data collection techniques in the form of observation, interviews and documentation. The primary data in this research are land owners and casual daily workers. The research results state that land owner literacy regarding the ujrah granting system is still very low due to: firstly, lack of understanding, land owners do not yet understand what ujrah is and how it works financially. Second, there is a lack of financial education, there is no adequate education regarding finances and debt management. Third, limited access to accurate and easy to understand information regarding ujrah by land owners, fourth, limited resources, land owners do not have the resources to obtain consultation or training. The welfare level of casual daily workers in Lubuk Tabun Village is relatively low, which is shown by the fact that many of them are still in a cycle of debt that is difficult to break. This happens because the income earned from working as a casual daily laborer is not sufficient to meet daily living needs